Momentos de aplicacion y eficiencia de fungicidas en el control de la sarna del duraznero - Cragnolini, C.I.=700 1 Novo, R.J.; March, G.J.; Conles, M.Y.; Balzarini, M.
(En, Es)
ilus., 24 ref.
Keywords: PRUNUS PERSICAE; CLADOSPORIUM; CLOROTALONIL; DODINA; FUNGICIDAS; ARGENTINA; CLADOSPORIUM CARPOPHILUM; DURAZNOS; POLISULFURO DE CALCIO